Kewenangan Daerah Dalam Negara Kesatuan Republik Indonesia - Hamid, Ahmad Farhan; Saripudin, Saripudin (Jurnal Konstitusi & Demokrasi, 2022)
This paper describes the development of the authority of the regional government in governmental affairs, and it closed by an effort to see the future of regional autonomy in the unity state of Indonesia.